Determination of the Level of Flatfoot in Children and Its Elimination (Texas Journal of Engineering and Technology, 2023)
According to statistics, congenital flatfoot in children is 3%. But as a result of wearing the wrong, cheap shoes, signs of flat feet are observed in 60-70% of children under 6 years of age. Flat feet abroad can be detected using computer pedometry (photo of footprints). The cost of this technology is much more expensive. A device has been developed that determines the level of flat feet. In the method proposed by us, the child's legs are diagnosed in strain sensitive elements, and the degree of the disease is fully determined